Design and synthesis of chroman derivatives with dual anti-breast cancer and antiepileptic activities - Rawat P; Verma SM (Dove Medical Press, 2016)
Pinki Rawat, Saurabh Manaswita Verma Department of Pharmaceutical Sciences and Technology, Birla Institute of Technology, Mesra, Ranchi, Jharkhand, India Abstract: A series of chroman derivatives was designed, prepared, and examined for their anti-breast cancer and antiepileptic activities. All synthesized compounds yielded results that were in good agreement with spectral data. The bioassay showed that some of the resultant compounds exerted remarkable inhibitory effects on growth of human breast cancer cell line MCF-7. In particular, compound 6i (the concentration required for 50% inhibition of cell growth [GI50] =34.7 µM) exerted promising anticancer activity toward MCF-7 cell line. Additionally, compounds 6b, 6c, 6d, 6e, 6g, 6i, and 6l showed advanced antiepileptic activity than reference drugs. None of the compounds showed neurotoxicity, as determined by the rotarod test. The obtained results proved that these distinctive compounds could be relevant as models for future discovery and research, as well as for the production of more number of active derivatives. Keywords: anti-breast cancer, antiepileptic, chroman, isatin, Schiff base